Penanaman Nilai-nilai Tasawuf dalam Rangka Pembinaan Akhlak di Sekiolah Melalui Kegiatan Ekstrakurikuler Keagamaan - Asep Kurniawan (AL-TAHRIR, 2013)
Abstract: Education is every single effort to maintain and develop human nature both esoteric and exoteric aspects. Reality in education shows that the human esoteric aspect left behind far from the progress of exoteric. Wrong paradigm that limits religious knowledge just in Islamic schools or Islamic boarding schools gradually can dissociate public school students from education of faith and devotion. Consequently, the orientation of education in schools turns into more materialistic, individualistic, and secularistic. Thus, there is a massive reduction of human existence itself. To overcome this, it is noteworthy to reorient education towards the holistic education with investment values of religious spirituality (Sufism) to get closer to God through Islamic extracurricular in school. This solution will make vertical integration of submission to God and horizontally dialectical dimension to humanity and the environment. The integration produces an educational output, such as students with righteous personality and noble behavior. Therefore, it can be understood that the values of Sufism are very esensial and cannot be separated from the educational problem-solving.